Penerapan Metode Pembelajaran Positivisme Menggunakan Video Pembelajaran untuk Meningkatkan Hasil Belajar Siswa Kelas XI SMK Plus Pertiwi (Indo-MathEdu Intellectuals Journal, 2024)
The research aims to determine the application of the positivism (quantitative) learning method in the subject "Basics of Photography" in class XI DKV SMK Plus Pertiwi Sukamulya Kuningan with the help of learning video media using the Wondershare Filmora application. This study uses the Pre-Experiment with One Group Pre-Test and Post-Test Design research method. The data collection techniques used are observation, interviews, tests and documentation of activities. The research sample consisted of grade XI students of Visual Communication Design (DKV) by being given a pretest to measure their initial ability in learning the basics of Photography. The data from the pretest and posttest results were analyzed using descriptive and inferential statistics assisted by SPSS and Microsoft Excel applications. The results of the research before being given treatment (pretest) received the highest score of 80, the lowest score of 40 and the average was 59. Then the results after being given treatment (posttest) by obtaining the highest score of 93, the lowest score of 60 and the average score of 77, the average increase in the score from pretest to posttest was 18. So it can be concluded that the results of the posttest obtained a higher average score compared to the pretest score, and there was a significant difference in value between the pretest and the posttest